Effects of customer's ICT investment and quality control activities on ICT investment decision and data sharing and usage along production networks in Southeast Asia - Yasushi Ueki; Masatsugu Tsuji (International Telecommunications Society (ITS), 2019)
Information and communication technologies (ICTs) generate externalities. A firm adopted an ICT will encourage its partner firms to adopt the compatible ICT to benefit fully from its own ICT investment. Thus, the firm and its partner firms who are collaborative and willing to adopt ICTs are like to transform their collaborations into digital based. Because small group activities for continuous improvement will develop organizational routines for information sharing within and between firms, firms promoting such activities are like to adopt ICTs. This study examines these hypotheses by using a survey data collected in Lao PDR, Thailand, and Vietnam in 2017. Results of two-stage least squares (2SLS) estimations present (1) significant relationships of customer's ICT investments and quality control circle with own ICT investment decision or planning and (2) significant relationships of the adoption of ICTs with data sharing within and between firms and effective data use. The findings suggest that (1) benefits from ICTs can be diffused along production networks even if firms reactively adopt ICTs and (2) policies for promoting ICT adoption, in tandem with quality management will improve the operation of entire production networks.
Keywords: 330; Information and communication technology (ICT); management information system (MIS); network effect; two-stage least squared; Southeast Asia